2017
DOI: 10.1016/s0140-6736(17)33176-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outpatient experience of Chinese public hospitals: a cross-sectional study

Abstract: Background Patient experience is an important indicator of health-care quality from the patient's view and has a better evidence-based characteristic than patient satisfaction. In this study, we compared the experience among different outpatient groups and explored the influencing factors of the outpatient experience to improve outpatient experience and the health-service quality of public hospitals in China.Methods Six comprehensive public hospitals in Hubei, China, were chosen by typical sampling method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…After a full-text review of these 226 studies, 190 studies were excluded with the reasons ( Supplementary Material 3 ). A total of 36 articles reported 35 studies that met the inclusion criteria of this review [ 7 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. All studies were published in peer-reviewed journals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a full-text review of these 226 studies, 190 studies were excluded with the reasons ( Supplementary Material 3 ). A total of 36 articles reported 35 studies that met the inclusion criteria of this review [ 7 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. All studies were published in peer-reviewed journals.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in peer-reviewed journals. Six of the studies were published in English [ 7 , 15 , 18 , 26 , 28 , 31 ], and 30 of the studies were published in Chinese. The selection process is summarized in Prisma searching flow diagram ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the problems of registration difficulty and slow payment have been alleviated. 17 It has been confirmed that patients' medical experiences have been improved to some extent by mobile health apps and other information technologies in medical institutions.…”
Section: Discussionmentioning
confidence: 94%
“…This finding indicated the problem that obtaining medical services became expensive. 17 In response to this situation, the local government also launched related policies, including provincial-level pooled tendering and procurement and a "zeromarkup" (ie, no-profit) policy for medicines on the new National Essential Drugs List at the grassroots level to lower the drug prices. 3 The basic medical insurance system was improved, government subsidies for basic medical insurance for urban and rural residents were raised to 520 RMB, and serious illness insurance increased by 15 RMB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation